2004
DOI: 10.1210/me.2003-0476
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pathways of Angiotensin II-Induced Extracellularly Regulated Kinase 1/2 Phosphorylation in Specific Cell Types: Role of Heparin-Binding Epidermal Growth Factor

Abstract: Stimulation of the angiotensin II (Ang II) type 1 receptor (AT1-R) causes phosphorylation of extracellularly regulated kinases 1 and 2 (ERK1/2) via epidermal growth factor receptor (EGF-R) transactivation-dependent or -independent pathways in Ang II target cells. Here we examined the mechanisms involved in agonist-induced EGF-R transactivation and subsequent ERK1/2 phosphorylation in clone 9 (C9) hepatocytes, which express endogenous AT1-R, and COS-7 and human embryonic kidney (HEK) 293 cells transfected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 56 publications
10
77
2
Order By: Relevance
“…HER1/ EGFR and HER2 can be activated by stimuli that do not interact directly with these receptors, a process that can occur through ligand-dependent or -independent means (12,38). For example, stimulation of the angiotensin II receptor induces shedding of the EGFR ligand heparin-binding EGF, leading to activation of EGFR in hepatocytes (39). In contrast, agonists of G proteincoupled receptors (such as lysophosphatidic acid) phosphorylate EGFR directly through Src kinase-dependent phosphorylation (40).…”
Section: Discussionmentioning
confidence: 99%
“…HER1/ EGFR and HER2 can be activated by stimuli that do not interact directly with these receptors, a process that can occur through ligand-dependent or -independent means (12,38). For example, stimulation of the angiotensin II receptor induces shedding of the EGFR ligand heparin-binding EGF, leading to activation of EGFR in hepatocytes (39). In contrast, agonists of G proteincoupled receptors (such as lysophosphatidic acid) phosphorylate EGFR directly through Src kinase-dependent phosphorylation (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, this mutant is able to stimulate HB-EGF shedding and EGFR transactivation in our study. The mutant also stimulated ERK in COS7 cells that was blocked by an EGFR kinase inhibitor or a metalloprotease inhibitor (66). The discrepancy may be due to the different nature of the cells utilized together with distinct experimental strategies (Seta and Sadoshima used cells expressing an exogenous EGFR gene) (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that cell types exhibiting Ang II signaling through EGF-R activation include VSMCs, cardiac myocytes and fibroblasts, COS 7 cells, C9 hepatic cells, glomerular mesengial cells, prostrate stromal cells, anterior pituitary cells, and breast cancer cells [23]. However, the EGF-R transactivation does not appear to be a universal process and has a minor or no role in HEK 293 cells [23] and pre-glomerular smooth muscle cells [24].…”
Section: Discussionmentioning
confidence: 96%
“…In rat aortic VSMCs, EGF-R transactivation was shown to be crucial for Ang II mediated p42/p44 MAP kinases [10,14,16]; however, in human embryonic kidney (HEK) cells transfected with AT 1 -R [23] and preglomular smooth muscle cells expressing endogenous AT 1 -R [24], MAP kinase activation by Ang II has been shown to occur independent of EGF-R transactivation. Since involvement of caveolin-1 in AT 1 -R signaling has not been well studied in non-vascular smooth muscle cell types, we initiated studies to determine if exposure of WB cells (a continuously passaged rat liver cell line), which expresses endogenous AT 1 -R, to Ang II, causes tyrosine phosphorylation of caveolin-1 and transactivation of EGF-R. WB cells are epithelial cells that were originally isolated from the liver of adult rats [25,26] and they have been used by numerous investigators to study Ang IIinduced signal transduction pathways [25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%